Healthcare Costs and Resource Utilization in Patients with Infantile Spasms Treated with H.P. Acthar Gel®. Issue 8 (August 2016) - Gold, Laura; Schepman, Patricia; Wang, Wei-Jhih; Philbin, Michael; Niewoehner, John; Damal, Kavitha; Hansen, Ryan
Abstract Introduction The purpose of this study was to describe healthcare resource utilization and costs resulting from early (within 30 days of diagnosis) versus late (>30 days after diagnosis) treatment with prescriptions for H.P. Acthar® Gel (repository corticotropin injection; Acthar; Mallinckrodt) to manage infantile spasms (IS). Methods We included all patients in the Truven Health MarketScan® Commercial Claims and Encounters Database and the Truven Health MarketScan Multi-State Medicaid Database who were diagnosed with IS from 2007 to 2012. We performed unadjusted and adjusted regressions examining the relationship between healthcare resource utilization variables and their associated costs to compare outcomes in the early and late Acthar users. Results A total of 252 patients with IS who received Acthar fit our study criteria; 191 (76%) were early Acthar users. In adjusted analyses, we found that early Acthar use was associated with, on average, 3.8 fewer outpatient services (99% CI 0.7–6.7 fewer services). We did not find significant associations between early prescriptions for Acthar and number of hospitalizations, emergency room visits, prescription medications filled, or total costs of health services. Conclusion Patients prescribed Acthar within 30 days of their IS diagnoses tended to have fewer outpatient services performed compared to patients prescribed Acthar later in the disease process. Although additional research is needed to confirm these exploratory findings, physicians may consider early treatment with Acthar to manage IS. Funding This study was funded by a grant to the University of Washington from Mallinckrodt Pharmaceuticals.